2020
DOI: 10.1088/2053-1591/ab66ab
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photoresponse in ZnO nanorod array/p-GaN self-powered ultraviolet photodetectors via coupling with CuO nanostructures

Abstract: ZnO nanorod arrays (ZnO NRAs) coupled with coral-like CuO nanostructures (CuO CLNs) were prepared by low-temperature hydrothermal method. Self-powered ultraviolet (UV) photodetectors (PDs) based on ZnO NRAs/CuO CLNs/p-GaN heterostructure were fabricated via a direct-contact method. Under UV illumination (1.46 mW cm −2 ), the ratios of photocurrent to dark current (I photo /I dark ), photo-responsivity and specific detectivity for the ZnO NRAs/CuO CLNs/p-GaN heterojunction self-powered PD were estimated to be 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…This problem can be overcome by introducing graphene as an active layer in ZnO nanowires and GaN heterojunctions . Furthermore, CuO nanostructures can be used in between ZnO nanowires and a GaN layer for UV photodetection at 365 nm wavelength . ZnO nanowires are potential materials for switchable dual-response UV photodetectors: in direct current, ZnO nanowires have positive photoconductivity, while in alternating current, the photoconductivity can be either positive or negative, depending on the frequency, which allows fine tuning of the polarity of changes in light and dark resistance …”
Section: Superhydrophobic Zno Nanowire Applicationsmentioning
confidence: 99%
“…This problem can be overcome by introducing graphene as an active layer in ZnO nanowires and GaN heterojunctions . Furthermore, CuO nanostructures can be used in between ZnO nanowires and a GaN layer for UV photodetection at 365 nm wavelength . ZnO nanowires are potential materials for switchable dual-response UV photodetectors: in direct current, ZnO nanowires have positive photoconductivity, while in alternating current, the photoconductivity can be either positive or negative, depending on the frequency, which allows fine tuning of the polarity of changes in light and dark resistance …”
Section: Superhydrophobic Zno Nanowire Applicationsmentioning
confidence: 99%
“…The heterojunctions with lesser lattice mismatch can achieve high photoinduced charge carrier separation efficiency as well as their efficient opto-electrical transport . The impact of these heterojunction structures has been realized as increased photodetection, higher responsivity, as well as external quantum efficiency (EQE). So far, numerous heterojunction-based UV photodetectors such as p-NiO/n-ZnO, TiO 2 /SnO 2 , TiO 2 /NiO, Se/ZnO, ZnO/SnO 2 , ZnO/GaN, and so forth have been fabricated. Among them, the ZnO/GaN heterojunction-based UV photodetectors have attracted considerable attention because of their similar properties as of the epilayer (i.e., GaN) such as analogous crystalline wurtzite structure, better interface [minimum lattice mismatch (1.8%)], wide and direct band gap [ E gGaN (3.4 eV), E gZnO (3.3 eV)], high thermal coefficient, high carrier mobility, high chemical stability, higher resistance toward electric breakdown field, and so forth .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, nanostructured (ZnO-nanostructures/GaN-film) UV photodetectors have received considerable attention because of their high surface to volume ratio, which leads to higher photon absorption and correspondingly higher photostimulated charge carriers which enhance photo as well as electrical conductivities in the device. Vikas et al have fabricated an n-ZnO-NRs/p-GaN heterostructure-based UV detector which demonstrated a responsivity of 11 A/W and response time < ms from the device . Consequently, numerous ZnO-NR/GaN film nanostructure-based UV photodetectors have been fabricated as tabulated in Table , wherein a highest responsivity value of 437 A/W has been demonstrated by Chen and Lee using n-ZnO/i-ZnO-NRs/p-GaN film heterojunction-based UV photodetectors. More recently, Goswami et al have adopted a unique approach of ZnO-nanorod (ZnO-NR) over GaN-nanotower (GaN-NT) structures to absorb maximum UV photons and realized a highly responsive UV photodetector with a responsivity of 1200 A/W …”
Section: Introductionmentioning
confidence: 99%
“…13–17 ZnO-based UV PDs, especially the self-powered ones, have been widely studied. 18–41 According to the interface structures, the reported self-powered ZnO-based UV PDs typically have two configurations including Schottky junctions 18–21 and p–n heterojunctions, 12–41 in which the built-in electric field produces a photovoltaic effect, leading to the separation and directional movement of the photogenerated electrons and holes. It has been demonstrated that a ZnO-based Schottky junction could be created by utilizing asymmetric electrodes or different contact models in the metal–semiconductor–metal structured UV PDs.…”
Section: Introductionmentioning
confidence: 99%
“…18,21 In contrast, ZnO-based p-n heterojunction devices with easy fabrication processes and low response times are ideal candidates for selfpowered UV PDs. 10 Various p-type materials such as Si, 22,23 GaN, 24,25 CuO, 26 NiO, 27,28 Ga 2 O 3 , 29,30 CuS-ZnS, 31 reduced graphene oxide (rGO), 33 conducting polymers, [35][36][37][38] CsPbBr 3 , 39 2,2 0 ,7,7 0tetrakis (N,N-di-p-methoxyphenylamine), 9,9 0 -spirobifluorene (Spiro-MeOTAD) 40 and poly(N-vinylcarbazole) (PVK) 41 are composited with ZnO to produce p-n heterojunctions for the fabrication of self-powered UV PDs. However, most of these devices are based on the thin-film p-n heterojunctions and electrodes, leading to a limited response speed, low transparency and bad flexibility.…”
Section: Introductionmentioning
confidence: 99%